Root rot fungi succession during cassava (Manihot esculenta. Crantz) tuberous development in different ecological zones of Nigeria - Aigbe, S.O.; Remison, S.U.; Bandyopadhyay, Ranajit (2008)
Root rot fungi succession during cassava tuberous root development was investigated in Ibadan (Derived savanna), Sabongidda-Ora and Onne (Humid forests) of Nigeria. Two improved cassava varieties (TMS 30572 and TMS 4 (2) 1425) and one local (TME-1) were planted in a randomized complete block design with 3 replications. Isolation of associated fungi was done from tuberous and fibrous root samples collected at 3, 6, 9 and 12 months after planting (MAP). Six species (Fusarium solani, Fusarium oxysporum, Botryodiplodia theobromae, Trichoderma harzianum, Rhizopus stolonifer, Aspergillus niger) and one unknown fungus were isolated frequently from growing roots. A clear relationship was demonstrated between growth stage, location, fungal succession and root rot incidence/severity. During the two planting seasons of this study and also throughout all locations, fibrous roots generally supported more diversity and higher frequencies of fungal growth than the tuberous roots. Fusarium oxysporum was usually an early to mid stage colonizer of root tissue while B. theobromae was a late colonizer. Botryodiplodia theobromae and F. solani were normally absent or rare during dry season periods at 6 MAP but re-emerged when rainy season resumed at 9 MAP till 12 MAP. Fusarium oxysporum dominated during the dry season period at 6 MAP. In the trial, local TME-1 genotype was the most colonized while improved TMS 4(2)1425 genotype was least colonized. In Ibadan and Sabongidda-Ora during the first planting season, F. solani was the most prevalent colonizer while B. theobromae was the most prevalent in Onne.